Role of B-Scan Ultrasonography in Pre-Operative Cataract Patients Attending Services Hospital, Lahore - Muhammad Asad Ullah, Rabia Yaseen, Abeera Afzal Buzdar, Haroon Saleem, Zafar Iqbal, Abdul Rafe (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The present study aimed to assess the role of B-scan in pre-operative cataract patients. Material and Methods: This prospective diagnostic study was conducted on 94 cataract patients in Ophthalmology Department, Services Hospital, Lahore from January 2021 to June 2021. Patients of either gender regardless of age having cataract were enrolled. Clinical history, detailed examination, and B-scan ultrasound of each individual was recorded. Individuals were examined in a lie supine position on the table and contact method was used. Coupling gel was applied and a probe was placed on the closed eyelid. B-scan ultrasound took images of different sections such as longitudinal, axial, and transverse sections. Resolution of the images was optimized by maintaining adequate intensity with the lowest possible decibel gain. Results: Out of 94 cataract patients, the number of male and female patients was 54 (57.4%) and 40 (42.6%) respectively. The incidence of traumatic and non-traumatic cataract patients was 20 (21%) and 74 (79%) respectively. About 42 (44.7%) cataract patients had a rural background and 52 (55.3%) had an urban background. The age distribution of cataract patients was as follows: 12 (12.8%) 1-20 years, 4 (4.3%) in 21-30 years, 19 (20.2%) in 31-40 years, 21 (22.3%) in 41-50 years, 32 (34%) in 51-60 years, and 6 (6.4%) >60 years. Of the traumatic cataract patients, posterior segment pathology was observed in 8 (40%) only whereas 12 (60%) had no posterior segment pathology. Out of traumatic cataract patient’s posterior segment pathology, the incidence of retinal detachment, vitreous hemorrhage, posterior vitreous detachment, intraocular foreign body and posterior staphyloma was 2 (25%), 1 (12.5%), 1 (12.5%), 3 (37.5%), and 0 (0%) respectively. Out of non-traumatic cataract patients, the incidence of posterior segment pathology and no posterior segment pathology was observed in 14 (18.9%) and 60 (81.1%) respectively. Among 14 posterior segment pathology, the incidence of retinal detachment, vitreous hemorrhage, posterior vitreous detachment, intraocular foreign body, and posterior staphyloma was 4 (28.6%), 3 (21.4%), 2 (14.3%), 2 (14.3%), and 3 (21.4%) respectively. Conclusion: The present study found that B-scan is a better diagnostic modality for the detection of posterior segment pathology in traumatic and non-traumatic cataract patients. Two dimensional B-scan can be effective in routine examination of pre-operative cataract patients. Three-dimensional B-scan could be considered in cases where two-dimensional does not provide sufficient help in assessment of posterior segment pathology in cataract patients. Keywords: Cataract patients, Traumatic cataract patients, Non-traumatic cataract patients, B-scan